1990
DOI: 10.1080/01904169009364064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutrient solution phosphorus concentration on potato plantlet tuber production under greenhouse conditions1

Abstract: Phosphorus fertilizer management of greenhouse grown micropropagated potato plantlets has been based on field research. Differences in growing conditions, potting media and the planting material itself may make the field research data base unacceptable in a greenhouse environment. This study was conducted to determine the optimum nutrient solution phosphorus (P) concentration for maximum growth and yield of micropropagated potato plantlets grown under greenhouse conditions. Nutrient solution P concentrations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Moreover, T Levels of Cu and Zn in fruits and vegetables did not also appear to expose serious health problems (43). Another study (44,45) also showed that P fertilizers might cause a linear increase in P concentration of plants. Therefore, the higher amount of P in plants in this study might be due to the extreme application of chemical P fertilizers.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, T Levels of Cu and Zn in fruits and vegetables did not also appear to expose serious health problems (43). Another study (44,45) also showed that P fertilizers might cause a linear increase in P concentration of plants. Therefore, the higher amount of P in plants in this study might be due to the extreme application of chemical P fertilizers.…”
Section: Discussionmentioning
confidence: 96%
“…The growing medium was a mix of 0.8 L L −1 vermiculite (Fafard et Frères Inc., Quebec, Canada) and 0.2 L L −1 quartz sand (Unimin Corp., New Canaan, CT, USA), washed with demineralized water before planting (Tukaki and Mahler, 1990). From emergence to the end of experiment, control plants were fertilized using a complete mineral solution made of Ca(NO 3 ) 2 ·4H 2 O, MgSO 4 ·7H 2 O, CaCl 2 , KH 2 PO 4, KNO 3 , Fe chelate (13.3%), Mn chelate, borax, Zn chelate, Cu chelate, and Na 2 MoO 4 ·2H 2 O and corresponding to 100% of nutrient in mineral solution (160 mg N L −1 , 29 mg P L −1 , 234 mg K L −1 , 160 mg Ca L −1 , 48 mg Mg L −1 , 62 mg S L −1 , 1.83 mg Fe L −1 , 0.5 mg Mn L −1 , 0.5 mg B L −1 , 0.05 mg Zn L −1 , 0.02 mg Cu L −1 , and 0.01 mg Mn L −1 ) (Tukaki and Mahler, 1990). To induce mineral deficiencies, other plants received modified mineral solutions providing 15, 30, or 60% of total N, K, or Mg concentrations received by the control treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Yield stability under environmental stresses, is an important focus for potato breeding, as potato is considered to be especially sensitive to osmotic stresses like drought (Vasquez‐Robinet et al ) or salt stress (Bilski et al ). Other environmental factors that can impact the productivity of potato are low temperature (Chen and Li , Kikuchi et al ) and nutritional deficiencies, such as phosphate (Tukaki and Mahler , Westermann et al ). Only a few studies have so far made use of CF imaging techniques for stress quantification in different potato genotypes.…”
Section: Introductionmentioning
confidence: 99%